2016
DOI: 10.5966/sctm.2015-0372
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Stem Cell Interventions for People With Cerebral Palsy: Systematic Review With Meta-Analysis

Abstract: Evidence for stem cells as a potential intervention for cerebral palsy is emerging. Our objective was to determine the efficacy and safety of stem cells for improving motor and cognitive function of people with cerebral palsy. Searches were conducted in October 2015 in CENTRAL, EMBASE, MEDLINE, and Cochrane Libraries. Randomized controlled trials and controlled clinical trials of stem cells for cerebral palsy were included. Two authors independently decided upon included trials, extracted data, quality, and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 30 publications
1
89
0
8
Order By: Relevance
“…Among medical interventions, autologous stem‐cell therapy was a prominent intervention used by Indian physicians, supposedly to improve a child's function. Evidence suggests that stem‐cell therapy is generally well tolerated and may provide short‐term improvements in motor skills (although the quality of the evidence is not strong); clearly, large and rigorous trials are needed to establish effectiveness . Weak‐to‐non‐existent regulations and policies to safeguard patients against exploitation and harmful exposure to unproven treatments (including stem‐cell ‘therapy’) contribute to encourage a flourishing stem‐cell tourism in India .…”
Section: Discussionmentioning
confidence: 99%
“…Among medical interventions, autologous stem‐cell therapy was a prominent intervention used by Indian physicians, supposedly to improve a child's function. Evidence suggests that stem‐cell therapy is generally well tolerated and may provide short‐term improvements in motor skills (although the quality of the evidence is not strong); clearly, large and rigorous trials are needed to establish effectiveness . Weak‐to‐non‐existent regulations and policies to safeguard patients against exploitation and harmful exposure to unproven treatments (including stem‐cell ‘therapy’) contribute to encourage a flourishing stem‐cell tourism in India .…”
Section: Discussionmentioning
confidence: 99%
“…UCB cells are safe and feasible as a therapeutic option in children with CP, and a recent meta-analysis investigating the efficacy of UCB across randomised controlled trials has demonstrated that UCB, alongside rehabilitation, is more effective at improving motor deficits than rehabilitation alone [14]. However, this preclinical animal study is the first to show that human UCB cells are protective for white matter development specifically in response to an inflammatory insult.…”
Section: Discussionmentioning
confidence: 64%
“…There is growing interest in the use of human umbilical cord blood (UCB) cells as a neuroprotective/neuroregenerative therapy for neurological disorders, in both paediatric and adult medicine [14]. Indeed, there are a number of clinical trials for the examination of UCB in infants and children with CP [15], and results to date support that UCB transplantation in children with established CP is associated with improved motor function with a low risk of adverse events [16].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have demonstrated the safety of UCB administration to children with established CP (Lee et al, 2012; Feng et al, 2015; Novak et al, 2016). Currently, however, it remains unclear how effective UCB could be in the setting of chorioamnionitis and preterm birth.…”
Section: Stem Cell Therapiesmentioning
confidence: 99%
“…Novak and colleagues recently reviewed the evidence for the use of stem cells in improving gross motor function in children with CP (Novak et al, 2016); four randomized clinical trials and one non-randomized clinical trial were included for analysis. Two of these trials involved the use of allogeneic UCB transplantation (Min et al, 2013; Kang et al, 2015).…”
Section: Stem Cell Therapiesmentioning
confidence: 99%